Parents' Perspectives on Family‐centered Care in Juvenile Justice Institutions. (2nd September 2018) - Simons, Inge; van der Vaart, Wander; Mulder, Eva; Rigter, Henk; Breuk, René; van Domburgh, Lieke; Vermeiren, Robert
Abstract: Family‐centered care during adolescent detention aims to increase parental participation in an attempt to optimize treatment outcomes. However, little is known about parents' needs in family‐centered care. To fill this gap, we interviewed 19 purposefully selected parents of detained adolescents using a semi‐structured topic list. Although needs differed between parents, they were generally interested in activities that included spending time with their child. It is important for parents to receive timely information about their child's condition and treatment, detention procedures, and activities in the facility. The outcomes demonstrated that parents expected a two‐way communication based on respect and reliability.